Chemical Bonding and Dynamic Structural Fluxionality of a Boron-Based B8Al3+ Cluster - Shu-Juan Gao; Tan-Lai Yu (Molecules)
We studied the boron-based composite cluster B8Al3+ doped with Al atoms. The global minimum structure of the B8Al3+ cluster is a three-layer structure, consisting of three parts: an Al2 unit, a B8 ring and an isolated Al atom. Charge calculations analysis shows that the cluster can be expressed as [Al]+[B8]2−[Al2]2+, has 6π/6σ double aromaticity and follows the (4n+2) Hückel rule. Born–Oppenheimer molecular dynamics (BOMD) simulation shows that the B8Al3+ cluster has dynamic fluxionality properties. Remarkably, at the single-point coupled cluster singles, doubles and triples (CCSD(T)) level, the energy barrier for intramolecular rotation is merely 0.19 kcal mol−1. [B8]2− molecular wheels have magical 6π/6σ double aromaticity properties, providing a continuous cloud of delocalized electrons, which is a key factor in the dynamic fluxionality of the cluster. The B8Al3+ cluster provides a new example of dynamic structural fluxionality in molecular systems.